Case Syncretism, Animacy, and Word Order in Continental West Germanic: Neurolinguistic Evidence from a Comparative Study on Standard German, Zurich German, and Fering (North Frisian). Issue 3 (September 2020) - Dröge, Alexander; Rabs, Elisabeth; Fleischer, Jürg; Billion, Sara K. H.; Meyer, Martin; Schmid, Stephan; Schlesewsky, Matthias; Bornkessel-Schlesewsky, Ina
Abstract : To understand a sentence, it is crucial to understand who is doing what. The interplay of morphological case marking, argument serialization, and animacy provides linguistic cues for the processing system to rapidly identify the thematic roles of the arguments. The present event-related brain potential (ERP) study investigates on-line brain responses during argument identification in Zurich German, a High Alemannic dialect, and in Fering, a North Frisian variety, which both exhibit reduced case systems as compared to Standard German. Like Standard German, Zurich German and Fering are Continental West Germanic varieties, and indeed argument processing in sentences with an object-before-subject order engenders a qualitatively similar ERP pattern of a scrambling negativity followed by a P600 in all tested varieties. However, the P600 component—a late positive ERP response, which has been linked to the categorization of task-relevant stimuli—is selectively affected by the most prominent cue for argument identification in each variety, which is case marking in Standard German, but animacy in Zurich German and Fering. Thus, even closely related varieties may employ different processing strategies based on the language-specific availability of syntactic and semantic cues for argument identification.*